Autophagy Induction by Endothelial-Monocyte Activating Polypeptide II Contributes to the Inhibition of Malignant Biological Behaviors by the Combination of EMAP II with Rapamycin in Human Glioblastoma - Ma, Jun; Meng, Fanjie; Li, Shuai; Liu, Libo; Zhao, Lini; Liu, Yunhui; Hu, Yi; Li, Zhen; Yao, Yilong; Xi, Zhuo; Teng, Hao; Xue, Yixue (Frontiers in Molecular Neuroscience, 2015)
This study aims to investigate the effect of endothelial-monocyte activating polypeptide II (EMAP II) on human glioblastoma (GBM) cells and glioblastoma stem cells (GSCs) as well as its possible mechanisms. In this study, EMAP II inhibited the cell viability and decreased the mitochondrial membrane potential in human GBM cells and GSCs, and autophagy inhibitor 3-methyl adenine (3-MA) blocked these effects. Autophagic vacuoles were formed in these cells after EMAP II treatment and this phenomenon was blocked by 3-MA. In addition, the up-regulation of microtubule-associated protein-1 light chain-3 (LC3)-II and the down-regulation of autophagic degraded substrate p62/SQSTM1 caused by EMAP II were observed. Cells treated with EMAP-II inhibited the PI3K/Akt/mTOR signal pathway, and PI3K/Akt agonist insulin-like growth factor-1 (IGF-1) blocked the effect of EMAP II on the expression of LC3-II and p62/SQSTM1. Cells exposed to EMAP-II experienced mitophagy and ER stress. Furthermore, the inhibition of cell proliferation, migration and invasion of GBM cells and GSCs were more remarkable by the combination of EMAP II and rapamycin than either agent alone in vitro and in vivo. The current study demonstrated that the cytotoxicity of EMAP II in human GBM cells and GSCs was induced by autophagy, accompanied by the inhibition of PI3K/Akt/mTOR signal pathway, mitophagy and ER stress. The combination of EMAP II with rapamycin demonstrated the inhibitory effect on the malignant biological behaviors of human GBM cells and GSCs in vitro and in vivo.